Implementasi Kesenian Sintren Melalui Literasi Budaya Dan Kewarganegaraan Pada Siswa Sekolah Dasar - Mae Afriliani; Dini Anggraeni Dewi; Rizky Saeful Hayat (Pendekar : Jurnal Pendidikan Berkarakter, 2024)
Sintren art is displayed at village clean-up events, harvest parties, almsgiving and celebrations. The aim of this research is to practice Sintren arts through the cultural and civic literacy of elementary school students. This type of research is library research. Sintren is a form of folk art from the Coast of Central Java and West Java. The Sintren arts performance venue is an open arena. This is to ensure that there are no barriers between the audience, Sintren dancers and their supporters during the performance.